Influence of open-switch failures on DC-link capacitors in hybrid ANPC inverters - Jo, Ha Rang; Ko, Youngjong; Lee, Kyo Beum (Journal of Power Electronics, 2021)
This paper analyzes the influence of a DC-link capacitor under open-switch failures in hybrid active neutral point clamped (ANPC) inverters that consist of Si-IGBTs and SiC-MOSFETs. Open-switch failures cause the current harmonic distortion of DC-link capacitors. This distorted current affects the capacitor loss increase, which in turn affects the lifetime decrement of the DC-link capacitor. These influences of open-switch failures on inverter operation have not been discussed despite the fact that they lead to secondary failures of the system. In this paper, the influence of open-switch failure is analyzed based on the current harmonics of the DC-link capacitor, which experiences the highest failure rate. Simulation and experimental results demonstrate the effects of various open-switch failure scenarios on DC-link capacitors in terms of current harmonics and lifetime.
Keywords: Active neutral point clamped; Capacitor lifetime; Current harmonics; Dc-link; Hybrid active neutral point clamped; Neutral point current harmonic; Neutral points; Open-switch failure; Point currents; Switch failure; Capacitor lifetime; Hybrid ANPC; Neutral point current harmonics; Open-switch failure